Infant morbidity in an Indian slum birth cohort. Issue 6 (4th October 2007) - Gladstone, B P; Muliyil, J P; Jaffar, S; Wheeler, J G; Le Fevre, A; Iturriza-Gomara, M; Gray, J J; Bose, A; Estes, M K; Brown, D W; Kang, G
Abstract : Objective: To establish incidence rates, clinic referrals, hospitalisations, mortality rates and baseline determinants of morbidity among infants in an Indian slum. Design: A community-based birth cohort with twice-weekly surveillance. Setting: Vellore, South India. Subjects: 452 newborns recruited over 18 months, followed through infancy. Main outcome measures: Incidence rates of gastrointestinal illness, respiratory illness, undifferentiated fever, other infections and non-infectious morbidity; rates of community-based diagnoses, clinic visits and hospitalisation; and rate ratios of baseline factors for morbidity. Results: Infants experienced 12 episodes (95% confidence interval (CI) 11 to 13) of illness, spending about one fifth of their infancy with an illness. Respiratory and gastrointestinal symptoms were most common with incidence rates (95% CI) of 7.4 (6.9 to 7.9) and 3.6 (3.3 to 3.9) episodes per child-year. Factors independently associated with a higher incidence of respiratory and gastrointestinal illness were age (3–5 months), male sex, cold/wet season and household involved in beedi work. The rate (95% CI) of hospitalisation, mainly for respiratory and gastrointestinal illness, was 0.28 (0.22 to 0.35) per child-year. Conclusions: The morbidity burden due to respiratory and gastrointestinal illness is high in a South Indian urban slum, with children ill for approximately one fifth of infancy, mainly with respiratory and gastrointestinal illnesses. The risk factors identified were younger age, male sex, cold/wet season and household involvement in beedi work.